Effects of carbon nanotube concentration on heat transfer characteristics in turbulent mixtures - Javad Zareei; John William Grimaldo Guerrero; Shoira Formanova; KDV Prasad; Sabir Tagelsir Hassan Widatalla (International Journal of Thermofluids)
This study presents numerical simulations modeling convective heat transfer in turbulent flows of carbon nanotube (CNT) mixtures suspended in water. The RNG k-ε turbulence model is employed and simulations are performed using the FLUENT software. The effects of varying nanoparticle concentration on the heat transfer characteristics are investigated. The results indicate that the presence of nanoparticles significantly increases the convective heat transfer coefficient, while their effect on pressure drop is minimal. The introduction of an excitation near the wall and the stimulation of the boundary layer further affect heat transfer, initially decreasing the heat transfer coefficient in the immediate vicinity, but significantly increasing it shortly thereafter. Incorporating CNTs into the base fluid at low volume fractions effectively improves heat transfer. In addition, positioning a barrier adjacent to the boundary layer results in a transient decrease in the heat transfer coefficient, followed by a significant increase. In particular, increasing the concentration of nanofluids from 0.1 % to 0.8 % leads to a remarkable increase in the heat transfer coefficient. However, further increasing the CNT concentration from 0.8 % to 1 % results in only a marginal increase in the heat transfer coefficient, accompanied by a significant increase in the frictional pressure drop.